Analisis Panjang Serat dan Durasi Perendaman NaOH terhadap Kekuatan Tarik Komposit Epoksi Berpenguat Bulu Kambing - Prima Rifqi Firdaus; Syamsul Hadi; Satria Ageng Gigih Santoso (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The problem with previous studies was the use of polyester resin as a matrix in kacang goat hair fiber composites, whereas in the latest study, epoxy resin was used, which has not been widely used. The aim was to obtain the tensile strength of composites that could be used as an alternative material for fan blades. The research method used was experimental with composite fabrication using the hand lay-up method, varying fiber lengths of 10 mm, 20 mm, and 30 mm, and varying immersion times in a 5% NaOH solution for 25, 50, 75, and 100 minutes. Tensile strength testing was carried out using the ASTM D638 standard with a total of 36 specimens. The test results showed that specimens with a fiber length of 30 mm and a soaking time of 50 minutes produced the highest tensile strength of 28.69 MPa, while the lowest tensile strength of 15.38 MPa was obtained in specimens with a fiber length of 10 mm and a soaking time of 100 minutes. This indicates that the highest tensile strength value is 46.37% greater than the lowest value, so the combination of a fiber length of 30 mm and a soaking time of 50 minutes is determined to be the optimal parameter in this study.